Labour market position of young people and premature mortality in adult life: A 26-year follow-up of 569 528 Swedish 18 year-olds - Nora Döring, PhD; Michael Lundberg, MSc; Christina Dalman, Prof; Tomas Hemmingsson, Prof; Finn Rasmussen, Prof; Alma Sörberg Wallin, PhD; Susanne Wicks, PhD; Cecilia Magnusson, Prof; Anton Lager, PhD (Elsevier, 2021)
Background: Throughout the industrialized world, demand for low skilled labour is falling. The length of schooling is increasing in response, but so is the proportion of individuals not finishing upper secondary school. The objective of this study was to evaluate the associations between labour market positions at age 18 and all-cause and suicide- and accident-specific mortality in later adulthood. Methods: Labour market positions at age 18 were categorized for all Swedes born 1972-77 (n=630 959) into four main groups: employed, successful students, students not about to qualify (SNAQs), and individuals not in employment, education or training (NEETs). Cox proportional hazard models were fitted to assess all-cause, suicide and accident mortality up to 2016 (ages 39-44), adjusting for high school grades, parental and own prior psychiatric diagnoses, and childhood socioeconomic status. Findings: SNAQs had substantially increased all-cause (men: HR=2.10; 95% CI 1.92-2.28, women: HR=1.64; 95% CI: 1.44-1.86), suicide (men: HR=2.16; CI: 1.86-2.51, women: HR=2.10; 95% CI 1.64-2.69), and accident specific (men: HR=2.08; 95% CI 1.77-2.44, women: 1.87; 95% CI 1.33;2.62) mortality risks compared to successful students. The risks were similar for NEETs. There was no increased risk among full-time employed compared to successful students. Interpretation: Expanding the educational system may be a natural response to falling demand for low skilled labour but not by far one that corrects the major societal challenge of it. Unless educational systems adequately respond to this challenge, only more inequality is to be expected ahead. Funding: This work was supported by a grant to FR and AL from the Swedish Research Council for Health, Working Life, and Welfare with contract number (2014-2009).